Antiviral Resistance and Hepatitis B Therapy - Ghany, Marc G. (2009)
The management of chronic hepatitis B currently rests with long-term therapy using oral nucleoside analogues. The major limitation of long-term therapy is antiviral resistance. Antiviral resistance is due to the high rate of mutations that can occur during hepatitis B virus (HBV) replication and the selection of these mutants due to a replication advantage in the presence of the antiviral agent. Indeed, high rates of antiviral resistance have been found with long-term use of lamivudine, in up to 76% of patients treated for 5 years or more. Rates of antiviral resistance are lower with adefovir therapy, ∼30% at 5 years. Newer more potent nucleoside analogues (tenofovir and entecavir) have proven to have much lower rates of antiviral resistance (<1% after 2 years in treatment-naïve subjects), but the long-term rates of resistance have yet to be fully defined. The appearance of these viral mutations (genotypic resistance) is usually followed by rises in HBV DNA levels (virological breakthrough) and then by rises in serum aminotransferase levels (biochemical breakthrough). The appearance of antiviral resistance can be accompanied by a transient but occasionally severe exacerbation of the underlying liver disease which in some instances have led to acute liver failure. Combinations of nucleoside analogues may offer an approach to preventing antiviral resistance, but the efficacy and safety of this approach has yet to be shown. A future research priority is to identify new agents active again HBV that target different steps in the viral life cycle and might provide effective means to circumvent the antiviral resistance of nucleoside analogues.